The Application Of Learnig Starts With A Question Strategy To Improve The Understanding Of Grade Iv Students In Natural And Social Science Subjects At Madrasah Ibtidaiyah Nurul Ittihad Jambi City - Ika Rahma; Sri Yulia Sari (PT. Anagata Sembagi Education, 2025)
This study was motivated by the results of initial observations in class IV with the problem of low learning quality and student understanding of the material taught. This research is a class action research (PTK) design model of Kemmis and Mc Taggart which consists of two cycles with the stages of planning, implementation, observation, and reflection which aims to overcome the problem of low student understanding through the application of the Learning Starts With A Question strategy in class IV Madrasah Ibtidaiyah Nurul Ittihad Jambi City. Data collection used are interviews, observations, tests and documentation. The results showed a significant increase in students' cognitive understanding in learning Natural and Social Sciences (IPAS) from pre-cycle to cycle II. In cycle I, the percentage of student completeness increased to 57.89% from 26% in the pre-cycle, and in cycle II it reached 84.21%, showing an increase of 53.21% from the pre-cycle. This research confirms that the Learning Starts With A Question Strategy is effective in improving students' understanding of students' cognitive in learning Natural and Social Sciences (IPAS). The implication of this research is the importance of choosing the right learning strategy to facilitate students' understanding of the subject matter being studied.